Lymphoepithelial Carcinoma of the Larynx: A Case Report - Muta, Michika; Maeda, Kotaro; Sato, Shunsuke; Kumai, Yoshihiko (International Journal of Practical Otolaryngology, 2025)
Lymphoepithelial carcinoma (LEC) is a rare malignancy that histologically resembles nonkeratotic nasopharyngeal carcinoma. Most head and neck LECs occur in the nasopharynx and are associated with Epstein–Barr virus infection, and non-nasopharyngeal LECs are extremely rare. Herein, we report a case of supraglottic LEC. The patient was a 73-year-old man in whom a laryngeal mass was incidentally detected during treatment for another disease. Computed tomography and magnetic resonance imaging revealed tumor invasion of the thyroid cartilage and a metastatic left cervical lymph node. The histological diagnosis was EBER(+) LEC, and the final diagnosis was supraglottic carcinoma (LEC, cT4aN2aM0). The patient was treated with neoadjuvant chemotherapy followed by surgery. At present, 8 months after the surgery, the patient remains under observation with no postoperative treatment, and no evidence of recurrence has been observed. In general, virus-associated cancers often have a better prognosis than nonvirus-associated cancers; however, the association between the prognosis of non-nasopharyngeal LEC and viral infection is currently unclear. Our experience with this case suggests that non-nasopharyngeal LEC could be effectively treated according to the treatment protocol for conventional squamous cell carcinoma of the head and neck with or without viral infection.
Keywords: lymphoepithelial carcinoma; Epstein–Barr virus; nonkeratinizing nasopharyngeal carcinoma